MnZn Ferrite

By optimizing the proportion of ingredients of MNZN iron oxygen body, especially when maintaining a high -increase magnetic guidance rate at low temperature and high temperature, the problem of decreased magnetic guidance rate in the temperature interval in the existing technology in the existing technology has increased. The qualification rate and inductance performance of the core.

CN119212963A9Active Publication Date: 2025-01-28JFE CHEMICAL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480001889.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-26
Filing Date
2024-04-18
Publication Date
2025-01-28
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

When the existing MnZn system ferrite is applied to a DC magnetic field in the temperature range of -40 to 85°C, the incremental permeability decreases at low temperatures and high temperatures. When manufacturing multiple ferrite cores, the characteristics deviation leads to the core. Low pass rate.

Method used

By optimizing the proportion of basic components and auxiliary components of MNZN, including the composition of iron, zinc, manganese, and the addition of Si, CA, CO, NB and V When M's DC magnetic field, the incremental magnetic guidance rate reaches 2800 or more.

Benefits of technology

When the temperature range of -40-85 ° C was applied to a 25A/m DC magnetic field, the incremental magnetic guidance rate of the MNZN iron oxygen body reached 2800 or more Electronic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212963A9_ABST
    Figure CN119212963A9_ABST
Patent Text Reader

Abstract

The present invention provides a MnZn ferrite suitable for electronic components such as pulse transformers. The MnZn ferrite can obtain a higher incremental magnetic permeability when a DC magnetic field of 25A / m is applied in a temperature range of -40 to 85°C. The MnZn ferrite of the present invention is composed of basic components, auxiliary components and inevitable impurities, wherein the basic components are: iron: 52.5-53.5 mol% calculated as Fe2O3; zinc: 16.4-18.4 mol% calculated as ZnO; and manganese: the balance calculated as MnO. Relative to the above basic components, the auxiliary components are: Si: 30-100 mass ppm calculated as SiO2; Ca: 50-160 mass ppm calculated as CaO; Co: 1500-3500 mass ppm calculated as Co3O4; Nb: 100-600 mass ppm calculated as Nb2O5; and V: 100-600 mass ppm calculated as V2O5, and the total content of the above Nb and the above V is 200-900 mass ppm calculated as Nb2O5 and V2O5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a MnZn ferrite suitable for electronic components such as pulse transformers, wherein the MnZn ferrite can obtain a high incremental magnetic permeability even when a DC magnetic field of 25 A / m is applied in a temperature range of -40 to 85°C. Background Art

[0002] In the transformer of Ethernet (registered trademark) equipment, a pulse transformer using soft magnetic materials in the magnetic core is used for the purpose of matching the impedance at the input and output terminals or maintaining electrical insulation. The pulse transformer is required to have high inductance, that is, high incremental permeability when a DC magnetic field is applied in a wide temperature range of -40 to 85°C. The incremental permeability is a value that represents the permeability (ease of magnetization) of the magnetic core when a magnetic field is applied. In addition, according to the literature, the term effective permeability is sometimes used instead of incremental permeability, but the two have the same meaning, so they are unified as incremental permeability from now on.

[0003] In the magnetic core composed of the above-mentioned soft magnetic materials, annular MnZn ferrite is usually used. Among many soft magnetic materials, MnZn ferrite is particularly easy to obtain high magnetic permeability and high inductance. In addition, compared with metal magnetic materials such as amorphous metals, MnZn ferrite has advantages such as low cost.

[0004] Here, MnZn-based ferrite has the characteristic that its magnetic properties greatly change with temperature fluctuations because it is an oxide magnetic material. Therefore, it has a disadvantage that it is difficult to obtain stable magnetic properties in a wide temperature range compared to metal magnetic materials.

[0005] Furthermore, pulse transformers are sometimes installed outdoors when used in line terminal equipment, etc. Therefore, MnZn-based ferrites used for pulse transformers are required to have high initial magnetic permeability in a wide temperature range from low to high temperatures, particularly in a temperature range of -40 to 85°C.

[0006] Furthermore, in digital communication equipment, a pulse transformer is sometimes operated by applying a DC magnetic field in a state where it is magnetized by the change in the positive and negative balance of the transmitted pulse voltage. Even in the state where such a DC magnetic field is applied, a high incremental permeability is required for signal conversion. In addition, in such applications, the size of the DC magnetic field applied will vary depending on the required inductance specifications, usage methods, etc., and a high incremental permeability is required at room temperature. In addition, in most cases, a general-purpose size MnZn-based ferrite core is used in a state where a maximum DC magnetic field of 25A / m is applied.

[0007] Here, the MnZn ferrite used in such a field is composed of Fe2O3, ZnO, and MnO as main components, and exhibits high magnetic permeability in the main components that make the magnetic anisotropy constant and magnetostriction constant zero. Therefore, the MnZn ferrite can be used as a small or thin magnetic core for transformers, noise filters, etc. That is, although there is a problem that it is difficult to obtain stable magnetic properties in a wide temperature range, a method for achieving high incremental magnetic permeability in a temperature range of -40 to 85°C (or -40 to 100°C) under a DC magnetic field is proposed.

[0008] For example, Patent Document 1 proposes a MnZn ferrite having an incremental magnetic permeability of 2000 or more when a DC magnetic field of 33 A / m higher than usual is applied in a temperature range of -40 to 85°C. In addition, Patent Document 2 proposes a MnZn ferrite having an incremental magnetic permeability of 2000 or more when a DC magnetic field of approximately 25 A / m is applied in a temperature range of -40 to 100°C.

[0009] In addition, in Patent Document 1, the following method is proposed: SiO2 and CaO are added simultaneously to the composition of MnZn ferrite (Fe2O3: 52.0~53.0mol%, ZnO: 22.0~23.0mol%, MnO: balance) that can obtain a high initial magnetic permeability, and the content of Cr2O3 as an impurity that is inevitably mixed in due to the raw material of iron oxide is reduced to an extremely small amount, thereby controlling the average crystal grain size of the MnZn ferrite within a suitable range, and obtaining a MnZn ferrite having an initial magnetic permeability of more than 10,000 (23°C) and an incremental magnetic permeability of more than 2,000 (-40~85°C, when a DC magnetic field of 33A / m is applied).

[0010] In Patent Document 2, the following method is proposed: in the main component composition of MnZn ferrite (Fe2O3: 51.0~52.0mol%, ZnO: 18.5~22.0mol%, MnO: balance), 0.5~1.5wt% of TiO2 and trace amounts of any of SiO2, CaO, V2O5, and Nb2O5 are contained as auxiliary components. Under the conditions of a residual magnetic flux density of less than 50mT and a magnetic bias of 135mT at room temperature (presumably due to the application of a DC magnetic field of 25A / m), a MnZn ferrite with a relative magnetic permeability of more than 2100 in the range of -40~100°C and little degradation of the DC superposition characteristics is obtained.

[0011] Patent document 3 proposes a method in which appropriate amounts of SiO2 and CaO are added to the basic composition of MnCoZn ferrite (Fe2O3: 51.0-53.0 mol%, ZnO: 13.0-18.0 mol%, CoO: 0.04-0.60 mol%, MnO: balance), TiO2 is used as an essential component, and the contents of P and B, which are inevitably mixed as impurities due to the raw material of iron oxide, are reduced to extremely small amounts, thereby obtaining MnCoZn ferrite whose incremental permeability shows a value of 2300 or more when a DC magnetic field of 33 A / m is applied over the entire temperature range of -40 to 85°C. In addition, in Patent document 3, since Co is contained, which shows an effect of flattening the temperature characteristics of the incremental permeability, a high Curie temperature of 140 to 210°C can be obtained in a wide composition range. Therefore, a high incremental permeability can be obtained even at low temperatures (-40°C) and high temperatures (85°C).

[0012] Furthermore, Patent Documents 4 and 5 disclose MnZn-based ferrites having a composition containing Ti and Bi.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Publication No. 2013-166663;

[0016] Patent document 2: Japanese Patent Application Publication No. 2004-319811;

[0017] Patent Document 3: Japanese Patent Application Publication No. 2008-143745;

[0018] Patent document 4: Japanese Patent Application Publication No. 2022-156991;

[0019] Patent document 5: China Patent Application Publication No. 1686927. Summary of the invention

[0020] Problem that the invention aims to solve

[0021] However, the MnZn-based ferrite obtained by the method described in Patent Document 1 does not contain an auxiliary component such as Co that flattens the temperature characteristics of the incremental permeability. Therefore, even under the condition of applying a mild DC magnetic field such as 25A / m, there is a problem that the incremental permeability at low temperatures (-40°C) and high temperatures (85°C) is lower than the value near room temperature. In addition, in the composition range described in Patent Document 1, the Curie temperature is as low as about 120 to 130°C, so there is inevitably a problem that the incremental permeability in the high temperature range above 85°C is lowered.

[0022] In addition, the MnZn-based ferrite obtained by the method described in Patent Document 2 does not contain an auxiliary component such as Co that flattens the temperature characteristics of the incremental permeability, so there is a problem that the incremental permeability at low temperatures (-40°C) and high temperatures (85°C) is lower than the value near room temperature. In addition, in the composition range described in Patent Document 2, since the Curie temperature is as low as 110 to 150°C, there is also a problem that the incremental permeability in the high temperature range above 85°C is lowered.

[0023] Furthermore, the invention described in Patent Document 3 contains a large amount of auxiliary components such as SiO2, CaO, ZrO2, Ta2O5, HfO2, and Nb2O5. Therefore, it can be considered that even if a DC magnetic field of 25A / m is applied, the incremental magnetic permeability in the range of -40 to 85°C will decrease as a whole.

[0024] Here, the incremental permeability of the MnZn ferrite shown in these documents that can be guaranteed in the range of -40 to 85°C is mostly around 2300. Although its characteristics are at a level that does not cause problems when used in ordinary pulse transformers, when multiple ferrite cores are manufactured, if the deviation of the characteristics is taken into account, there is a problem of low core qualification rate. In order to meet the requirements of improving the core qualification rate, reducing the number of copper wire windings, or further miniaturizing the core, it is necessary to ensure a higher incremental permeability, but the ability to cope with such problems is insufficient.

[0025] As in the inventions described in Patent Documents 4 and 5, if Ti is contained, the incremental magnetic permeability μ under the application of a DC magnetic field is dc The temperature characteristics of are shifted to the low temperature side, and the incremental permeability at high temperature decreases. In addition, if Bi is contained, the initial permeability increases when no DC magnetic field is applied, but the effective permeability μ decreases when a DC magnetic field is applied.

[0026] The present invention was developed in view of the above situation, and the purpose of the present invention is to provide a MnZn ferrite suitable for electronic components such as pulse transformers. The above-mentioned MnZn ferrite can obtain a higher incremental magnetic permeability when a DC magnetic field of 25A / m is applied in a temperature range of -40 to 85°C.

[0027] Solutions for solving problems

[0028] The present invention proposes a MnZn ferrite having an incremental magnetic permeability of 2800 or more when a DC magnetic field of 25 A / m is applied in a temperature range of -40 to 85°C. The incremental magnetic permeability needs to be increased in a wider temperature range, and the incremental magnetic permeability is particularly prone to decrease near -40°C and near 85°C. Therefore, in the present invention, the incremental magnetic permeability is set to be 2800 or more near -40°C and near 85°C. Furthermore, the temperature at which the incremental magnetic permeability takes a maximum value is preferably set in the range of 10 to 50°C. In addition, the MnZn ferrite preferably has an incremental magnetic permeability of 3700 or more in the temperature range of about 0 to 60°C, and an incremental magnetic permeability of 4100 or more in the temperature range of 23 to 40°C. In addition, in the present invention, the values ​​of the initial magnetic permeability and the incremental magnetic permeability are expressed as a ratio to the magnetic permeability μo of a vacuum (relative magnetic permeability).

[0029] That is, the main configuration of the present invention is as follows.

[0030] [1] A MnZn ferrite, which is composed of a basic component, an auxiliary component and inevitable impurities, wherein, when the total amount of iron, zinc and manganese is calculated as 100 mol%, the basic component is: iron: 52.5 to 53.5 mol% calculated as Fe2O3; zinc: 16.4 to 18.4 mol% calculated as ZnO; and manganese: the balance calculated as MnO, and the auxiliary component is: S i: 30 to 100 mass ppm calculated as SiO2; Ca: 50 to 160 mass ppm calculated as CaO; Co: 1500 to 3500 mass ppm calculated as Co3O4; Nb: 100 to 600 mass ppm calculated as Nb2O5; and V: 100 to 600 mass ppm calculated as V2O5, the total content of the above Nb and the above V being 200 to 900 mass ppm calculated as Nb2O5 and V2O5.

[0031] [2] The MnZn ferrite according to the above [1], wherein the incremental permeability of the MnZn ferrite is greater than 2800 when a DC magnetic field of 25 A / m is applied in a temperature range of -40 to 85°C, and the temperature showing the maximum value of the incremental permeability is in the range of 10 to 50°C.

[0032] [3] The MnZn ferrite according to the above [2], wherein the incremental permeability of the MnZn ferrite when a DC magnetic field of 25 A / m is applied in a temperature range of 0 to 60°C is greater than 3700, and further, the incremental permeability of the MnZn ferrite when a DC magnetic field of 25 A / m is applied in a temperature range of 23 to 40°C is greater than 4100.

[0033] Effects of the Invention

[0034] According to the present invention, a MnZn ferrite can be obtained which has an incremental magnetic permeability of 2800 or more at around -40°C and 85°C in the temperature range of -40 to 85°C when a DC magnetic field of 25A / m is applied. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The relationship between Fe2O3 content and incremental magnetic permeability (μ dc )’s impact.

[0036] Figure 2 The relationship between the ZnO content and the incremental magnetic permeability (μ dc )’s impact.

[0037] Figure 3 The figure shows the effect of SiO2 content on incremental magnetic permeability (μ) at various measurement temperatures. dc )’s impact.

[0038] Figure 4 The relationship between the CaO content and the incremental magnetic permeability (μ dc )’s impact.

[0039] Figure 5 The relationship between the Co3O4 content and the incremental magnetic permeability (μ dc )’s impact.

[0040] Figure 6 The results show the effect of Nb2O5 content and V2O5 content on the incremental magnetic permeability (μ dc )’s impact.

[0041] Figure 7 The incremental magnetic permeability (μ) at each measurement temperature of Comparative Example 13, Comparative Example 14 and Comparative Example 15 is shown. dc ) values. DETAILED DESCRIPTION

[0042] Hereinafter, one embodiment of the present invention will be described in detail. In addition, the embodiment described below is an example of specific embodiment of the present invention, and the configuration of the present invention is not limited to this specific example.

[0043] (MnZn ferrite)

[0044] MnZn ferrite is composed of basic components, auxiliary components and inevitable impurities. The basic components are composed of iron, zinc and manganese, and the above substances exist in the form of oxides. In addition, the following mol% is the composition ratio of the basic components.

[0045] [Incremental permeability]

[0046] First, each component will be described from the viewpoint of incremental magnetic permeability.

[0047] In the present invention, iron is contained in a range of 52.5 to 53.5 mol% in terms of Fe2O3 conversion. The iron content is preferably 52.6 mol% or more in terms of Fe2O3 conversion, and more preferably 52.7 mol% or more. On the other hand, the iron content is preferably 53.3 mol% or less in terms of Fe2O3 conversion, and more preferably 53.1 mol% or less. In the present invention, the reason for setting the iron content in terms of Fe2O3 conversion to 52.5 to 53.5 mol% is as follows. That is, this is because: when the iron content is around 53.0 mol% in terms of Fe2O3 conversion, the magnetostriction constant λ=0, and the incremental permeability when a DC magnetic field of 25 A / m is applied is the highest. On the other hand, when the iron content is less than 52.5 mol% in terms of Fe2O3 conversion or greater than 53.5 mol%, the incremental permeability is greatly reduced. In addition, as the iron content deviates from 53.0 mol% in terms of Fe2O3, the core expands and contracts more due to the application of a magnetic field, thereby applying more stress to the core itself, hindering the movement of the magnetic domain walls and significantly reducing the incremental permeability.

[0048] It is known that the Curie temperature and sub-peak of MnZn ferrites vary depending on the ratio of iron to zinc. In the present invention, 16.4 to 18.4 mol% of zinc is contained in terms of ZnO. In addition, the zinc content is preferably 16.5 mol% or more in terms of ZnO conversion, and more preferably 16.6 mol% or more. On the other hand, the zinc content is preferably 18.3 mol% or less in terms of ZnO conversion, and more preferably 18.2 mol% or less. The reason why the zinc content is set to the range of 16.4 to 18.4 mol% in terms of ZnO conversion is that the Curie temperature in this range is about 160 to 190°C, and good incremental permeability can be obtained even at high temperatures (85°C). In addition, if the zinc content is less than 16.4 mol% in terms of ZnO conversion, even if the Curie temperature becomes higher, the initial permeability itself will decrease, so the incremental permeability when a DC magnetic field is applied will also decrease. On the other hand, if the zinc content is greater than 18.4 mol % in terms of ZnO, the Curie temperature decreases, and therefore the incremental permeability at high temperature (85° C.) decreases.

[0049] Manganese is the balance of the basic components. It is preferably contained in the range of 28.0 to 31.0 mol% in terms of MnO. In addition, the manganese content is more preferably 28.5 mol% or more, and more preferably 30.7 mol% or less in terms of MnO.

[0050] That is, the basic components of MnZn-based ferrite are determined by taking the total of iron, zinc and manganese as 100 mol % in terms of Fe 2 O 3 , ZnO and MnO.

[0051] Next, the auxiliary components are described. The MnZn-based ferrite of the present invention preferably contains Si, Ca, Co, Nb and V as auxiliary components in addition to the above-mentioned basic components, and is composed of these. These exist in the form of oxides such as SiO2, CaO, Co3O4, Nb2O5 and V2O5, respectively. In addition, the content of the auxiliary components is expressed in mass ppm relative to the basic components.

[0052] Si and Ca are both elements that promote grain boundary formation, inhibit grain growth, and increase resistivity. By containing appropriate amounts of Si and Ca, the decrease in initial magnetic permeability can be suppressed as a whole in a wide temperature range of -40 to 85°C, and the incremental magnetic permeability in the low temperature range and the high temperature range can be increased when a DC magnetic field is applied, thereby obtaining a high incremental magnetic permeability in a wide temperature range of -40 to 85°C.

[0053] It is important that Si is contained in the range of 30 to 100 mass ppm in terms of SiO2 conversion, preferably 40 mass ppm or more, preferably 95 mass ppm or less. In addition, it is important that Ca is contained in the range of 50 to 160 mass ppm in terms of CaO conversion, preferably 90 mass ppm or more, preferably 150 mass ppm or less. In the case where Si is less than 30 mass ppm in terms of SiO2 conversion and Ca is less than 50 mass ppm in terms of CaO conversion, the incremental permeability in the low temperature range and the high temperature range decreases, and an incremental permeability of more than 2800 cannot be obtained in the wide temperature range of -40 to 85°C. On the other hand, in the case where Si is greater than 100 mass ppm in terms of SiO2 conversion and Ca is greater than 160 mass ppm in terms of CaO conversion, the incremental permeability is greatly reduced due to the significant reduction in the initial permeability, and an incremental permeability of more than 2800 cannot be obtained in the wide temperature range of -40 to 85°C.

[0054] Co is an effective component for improving the temperature dependence of the magnetic properties of MnZn ferrites. By containing an appropriate amount of Co, the change in incremental permeability relative to temperature when a DC magnetic field is applied becomes smaller, and the incremental permeability in the low temperature range and the high temperature range is improved. However, Co also has the effect of shifting the temperature dependence of the permeability toward the low temperature side. Therefore, if the Co content is too little or too much, the balance of the permeability in the low temperature range and the high temperature range is destroyed, and the incremental permeability in the low temperature range or the high temperature range is reduced, and thus a high incremental permeability cannot be obtained in a wide temperature range of -40 to 85°C.

[0055] It is important to contain Co in the range of 1500 to 3500 mass ppm in terms of Co3O4. In addition, Co preferably contains 1800 mass ppm or more, and more preferably contains 2000 mass ppm or more in terms of Co3O4. On the other hand, Co preferably contains 3000 mass ppm or less, and more preferably contains 2900 mass ppm or less in terms of Co3O4. In the case where Co is less than 1500 mass ppm in terms of Co3O4, the maximum point of the temperature characteristic of the incremental permeability shifts to the high temperature side, the incremental permeability at high temperature becomes better, but the characteristics at low temperature deteriorate, and thus the incremental permeability of more than 2800 cannot be obtained in a wide temperature range of -40 to 85°C. On the other hand, in the case where Co is greater than 3500 mass ppm in terms of Co3O4, the maximum point of the temperature characteristic of the incremental permeability shifts to the low temperature side, the low temperature characteristics of the incremental permeability become better, but the high temperature characteristics deteriorate, and thus the incremental permeability of more than 2800 cannot be obtained in a wide temperature range of -40 to 85°C.

[0056] Nb and V are elements that suppress the formation of coarse grains by coexistence, thereby obtaining fine and uniform grains and improving resistivity. By containing appropriate amounts of Nb and V, the incremental permeability when a DC magnetic field is applied can be improved.

[0057] It is important that Nb is contained in a range of 100 to 600 mass ppm in terms of Nb2O5, preferably 200 mass ppm or more, preferably 575 mass ppm or less. In addition, it is important that V is contained in a range of 100 to 600 mass ppm in terms of V2O5, preferably 200 mass ppm or more, preferably 400 mass ppm or less.

[0058] Furthermore, it is important that the total content of Nb and V in the MnZn-based ferrite is in the range of 200 to 900 mass ppm in terms of Nb2O5 and V2O5. The total content of Nb and V in terms of Nb2O5 and V2O5 is preferably 250 mass ppm or more and preferably 750 mass ppm or less.

[0059] In any case where Nb is less than 100 mass ppm in terms of Nb2O5, V is less than 100 mass ppm in terms of V2O5, or the total content of Nb and V is less than 200 mass ppm, the formation of coarse grains cannot be fully suppressed, and the resistivity is also low, so the incremental permeability when a DC magnetic field is applied will also decrease. On the other hand, in any case where Nb is greater than 600 mass ppm in terms of Nb2O5, V is greater than 600 mass ppm in terms of V2O5, or the total content of Nb and V is greater than 900 mass ppm, the grains will be refined and the resistivity will also increase, so the magnetic domain wall becomes difficult to move and the initial permeability decreases. The incremental permeability when a DC magnetic field is applied will also decrease accordingly.

[0060] [Defective rate caused by abnormal grain growth]

[0061] Next, each component is explained from the perspective of the defective rate caused by abnormal grain growth. Generally, auxiliary components such as Si or Ca added to MnZn ferrites have a great influence not only on the characteristics, but also on the formation of grains. In the case of containing an appropriate amount of auxiliary components, the auxiliary components are segregated at the grain boundaries, thereby having the function of inhibiting the coarsening of grains, making the crystal structure uniform, and improving the resistivity. However, the auxiliary components also have the effect of promoting sintering, so in the case of containing excessive auxiliary components, it is easy to cause abnormal grain growth, leading to the coarsening of grains. If coarse abnormal grains are generated, there is a problem of reduced resistivity, especially reduced incremental permeability in low temperature range and high temperature range. Ferrite cores that have generated abnormal grains of a certain size or more like this have problems in appearance and characteristics, and are therefore regarded as defective products. In addition, the abnormal grains present on the surface of the sintered core are different in color from the healthy ferrite sintered core, so they can be distinguished by visual inspection.

[0062] On the other hand, when the content of Si and Ca in MnZn ferrite is small, the generation of abnormal grains is suppressed, so there is a tendency to reduce the defect rate caused by abnormal grain growth. In addition, although the influence is not as great as that of Si or Ca, abnormal grain growth is also likely to occur when excessive Nb, V, Ti or Bi are contained in MnZn ferrite. Therefore, in order to reduce the defect rate caused by abnormal grain growth on the surface of the ferrite sintered core, it is important to reduce the content of auxiliary components that contribute greatly to the generation of abnormal grains.

[0063] In the present invention, the contents of the basic components and auxiliary components such as Si and Ca are appropriately selected in such a way that the initial magnetic permeability μi becomes high, so that basically there are the advantages of less generation of abnormal grains and low defective rate caused by abnormal grain growth of the ferrite core. That is, when Si is contained in the range of 30 to 100 mass ppm calculated as SiO2, and when Ca is contained in the range of 50 to 160 mass ppm calculated as CaO, the generation of abnormal grains is suppressed and the defective rate of the ferrite core becomes low. On the contrary, when Si is greater than 100 mass ppm calculated as SiO2, or when Ca is greater than 160 mass ppm calculated as CaO, there is a tendency that the generation of abnormal grains increases and the defective rate caused by abnormal grain growth of the ferrite core becomes higher.

[0064] Similarly, when the content of Nb or V is greater than 900 mass ppm in total as Nb2O5 conversion value and V2O5 conversion value, the defect rate caused by abnormal grain growth of the ferrite core becomes high. Therefore, the content of Nb or V is preferably set to 900 mass ppm or less in total as Nb2O5 conversion value and V2O5 conversion value. On the other hand, the content of Nb or V is preferably set to 200 mass ppm or more in total as Nb2O5 conversion value and V2O5 conversion value.

[0065] [Process capability index Cpk]

[0066] Next, each component is described from the perspective of the process capability index Cpk. Since the content of auxiliary components such as Si or Ca in the MnZn ferrite of one embodiment of the present invention is small, the incremental permeability will become the lowest value at any temperature of -40°C or 85°C in the temperature range of -40 to 85°C. The present MnZn ferrite has the characteristic that the deviation of the incremental permeability becomes smaller than that of ferrites with a high content of Si or Ca at this temperature. Therefore, the margin of the present MnZn ferrite relative to the lower limit specification of the incremental permeability taking into account the deviation is also good. Therefore, from the perspective of the defective generation rate below the lower limit specification of the incremental permeability, it is also preferred that the content of auxiliary components such as Si or Ca is small. That is, the MnZn ferrite with a small content of auxiliary components such as Si or Ca can obtain a high process capability index Cpk. In addition, Cpk is usually preferably above 1.33.

[0067] Therefore, from the viewpoint of obtaining a high process capability index Cpk, the total content of Si and Ca in the MnZn ferrite is preferably set to 260 mass ppm or less in terms of SiO2 and CaO conversion. On the other hand, the total content of Si and Ca in the MnZn ferrite can be set to 80 mass ppm or more in terms of SiO2 and CaO conversion.

[0068] The MnZn-based ferrite of the present invention may contain inevitable impurities such as P, B, S, and Cl. The content of the inevitable impurities is suppressed to a total of 500 mass ppm or less.

[0069] (Method for producing MnZn-based ferrite)

[0070] Next, the method for producing the MnZn-based ferrite of the present invention will be described.

[0071] The method for producing the MnZn-based ferrite of the present invention can use a known general production method. The general production method is as follows.

[0072] First, powder raw materials of Fe2O3, ZnO and Mn3O4 (the composition ratio is not converted to Mn3O4 but converted to MnO) as basic components are weighed in a manner to meet the amount specified in the present invention, and mixed by an attritor and a ball mill to obtain a mixed powder. The mixing method can be either a dry method or a wet method.

[0073] Next, the mixed powder is heated to a temperature in the range of 800 to 1000° C. for pre-calcination to obtain pre-calcined powder. Next, the pre-calcined powder is wet-pulverized using an attritor or a ball mill until the pulverized particle size is about 0.8 to 1.6 μm. At this time, an auxiliary component in an amount satisfying the amount specified in the present invention is added and pulverized. In this pulverization operation, a homogenization treatment is required so that the concentration of the auxiliary component is not biased.

[0074] An organic binder such as polyvinyl alcohol is added to the slurry obtained by the wet pulverization, and granulation is performed using a spray dryer or the like to obtain granulated powder. The granulated powder is then filled into a metal mold of a predetermined shape and molded to obtain a molded body. The molded body thus obtained is sintered to obtain a core of the MnZn ferrite according to the present invention.

[0075] The MnZn ferrite obtained by the present invention has an incremental permeability of 2800 or more when a DC magnetic field of 25A / m is applied in a temperature range of -40 to 85°C. Furthermore, it is preferred that the temperature at which the incremental permeability takes a maximum value is in the range of 10 to 50°C. Furthermore, it is preferred that the incremental permeability is 3700 or more when a DC magnetic field of 25A / m is applied in a temperature range of 0 to 60°C, and the incremental permeability is as high as 4100 or more when a DC magnetic field of 25A / m is applied in a temperature range of 23 to 40°C. In addition, since the incremental permeability of the MnZn ferrite is as high as 2800 or more, during mass production, the number of unqualified products due to substandard characteristics is reduced, and the effect of improving the yield can be achieved.

[0076] In addition, the incremental permeability of the core of the MnZn ferrite of the present invention is an upward convex curve showing a maximum value when a DC magnetic field of 25A / m is applied in the temperature range of -40 to 85°C. Here, the temperature at which the incremental permeability shows a maximum value is different from the temperature at which the initial permeability shows a secondary peak. If an appropriate amount of auxiliary components such as Co3O4 are added and the temperature at which the maximum value is shown is appropriate, a balance between the incremental permeability at low temperature (near -40°C) and high temperature (near 85°C) can be achieved, and the above-mentioned high incremental permeability can be stably obtained. That is, in the present invention, it is important to make the temperature at which the incremental permeability shows a maximum value within an appropriate range (in the range of 10 to 50°C) by containing appropriate basic components and auxiliary components. The temperature at which the incremental permeability shows a maximum value is preferably above 15°C, and preferably below 45°C.

[0077] Example

[0078] [Incremental permeability]

[0079] First, the influence of the basic components and auxiliary components on the incremental magnetic permeability was investigated. The raw material powders were weighed so that Fe2O3, ZnO and Mn3O4 (the compounding ratio was converted to MnO) which are the basic components of MnZn ferrite had the composition ratios shown in Tables 1 to 3. High-purity raw material powders were used.

[0080] Here, the components of Comparative Examples 13, 14, and 15 are respectively set to the components equivalent to Example 11 of Patent Document 4, Example 1 of Patent Document 5, and Example 2 of Patent Document 5. That is, the composition ratio of Fe2O3 and ZnO is set to the composition ratio described in each patent document, and MnO as the remainder is appropriately adjusted so that the total of the basic components becomes 100 mol%.

[0081] The raw material powders were mixed and crushed for 16 hours in a ball mill, and then pre-calcined at 925°C for 3 hours in the atmosphere to obtain pre-calcined powder. Then, SiO2, CaCo3, Co3O4, Nb2O5, V2O5, TiO2 and Bi2O5 were added to the pre-calcined powder in the composition ratios shown in Tables 1 to 3, and crushed in a ball mill for 12 hours to obtain crushed powder. Then, polyvinyl alcohol was added to the crushed powder for granulation, and a pressure of 118 MPa was applied to form a ring core to form a molded body. After that, the molded body was loaded into a sintering furnace and sintered at a maximum temperature of 1350°C to obtain a sintered body sample with an outer diameter of 30.5 mm, an inner diameter of 19 mm and a height of 6.5 mm. In addition, the contents of P, B, S, Cl and other inevitable impurities were quantitatively determined according to JIS K0102 (ICP mass analysis method) and confirmed to be less than 500 mass ppm. Each sample thus obtained was wound with 20 turns, and the initial permeability and incremental permeability were determined using a precision LCR meter E4980A (manufactured by Keysight Technologies). The initial permeability was measured at 23°C and 100kHz without superimposing a DC magnetic field. In addition, the temperature characteristics of the incremental permeability were measured at -40°C, 0°C, 23°C, 40°C, 60°C, and 85°C at a frequency of 100kHz with a DC magnetic field of 25A / m superimposed. The results are shown in Tables 1 to 3 and Figures 1 to 7 In addition, the solid line in the figure shows the incremental permeability (μ dc ) is the line for the case where 2800.

[0082] [Table 1]

[0083]

[0084] [Table 2]

[0085]

[0086] [Table 3]

[0087]

[0088] <Basic ingredients>

[0089] As shown in Table 1 and Figure 1 , 2As shown, from the results of Inventive Examples 1 to 8 and Comparative Examples 1 to 4, it can be seen that when Fe2O3 as a basic component is in the range of 52.5 to 53.5 mol% and ZnO is in the range of 16.4 to 18.4 mol%, when a DC magnetic field of 25 A / m is applied, an incremental permeability of 2800 or more can be obtained in the temperature range of -40 to 85°C, and the temperature at which the incremental permeability shows a maximum value is in the range of 10 to 50°C. In addition, in Inventive Examples 1 to 8, it can be seen that the incremental permeability is 3700 or more when a DC magnetic field of 25 A / m is applied in the temperature range of 0 to 60°C, and the incremental permeability is 4100 or more when a DC magnetic field of 25 A / m is applied in the temperature range of 23 to 40°C.

[0090] <Auxiliary component SiO2>

[0091] As shown in Table 2 and Figure 3 As shown, from the results of Invention Examples 9 to 11 and Comparative Examples 5 to 6, it can be seen that if SiO2 as an auxiliary component is in the range of 30 to 100 mass ppm, when a DC magnetic field of 25 A / m is applied, an incremental magnetic permeability of more than 2800 can be obtained in the temperature range of -40 to 85°C, and the temperature at which the incremental magnetic permeability shows a maximum value is in the range of 10 to 50°C.

[0092] <Auxiliary ingredient CaO>

[0093] As shown in Table 2 and Figure 4 As shown, from the results of Invention Examples 12 to 15 and Comparative Examples 7 to 8, it can be seen that if CaO as an auxiliary component is in the range of 50 to 160 mass ppm, when a DC magnetic field of 25 A / m is applied, an incremental magnetic permeability of more than 2800 can be obtained in the temperature range of -40 to 85°C, and the temperature at which the incremental magnetic permeability shows a maximum value is in the range of 10 to 50°C.

[0094] <Auxiliary ingredient Co3O4>

[0095] As shown in Table 2 and Figure 5 As shown, from the results of Inventive Examples 16 to 20 and Comparative Examples 9 to 10, it can be seen that if the Co3O4 as an auxiliary component is in the range of 1500 to 3500 mass ppm, when a DC magnetic field of 25A / m is applied, an incremental magnetic permeability of more than 2800 can be obtained in the temperature range of -40 to 85°C. In particular, the incremental magnetic permeability of Inventive Examples 17 to 20 shows a maximum temperature in the range of 10 to 50°C.

[0096] <Auxiliary components Nb2O5 and V2O5>

[0097] As shown in Table 2 and Figure 6As shown, from the results of Inventive Examples 21 to 24 and Comparative Examples 11 to 12, it can be seen that if Nb2O5 and V2O5 as auxiliary components are both in the range of 100 to 600 mass ppm, and the total of Nb2O5 and V2O5 is in the range of 200 to 900 mass ppm, then when a DC magnetic field of 25 A / m is applied, an incremental magnetic permeability of more than 2800 can be obtained in the temperature range of -40 to 85°C, and the temperature at which the incremental magnetic permeability shows a maximum value is in the range of 10 to 50°C.

[0098] <Case Equivalent to Patent Document 4: Comparative Example 13>

[0099] As shown in Table 3 and Figure 7 As shown, it can be seen that in Comparative Example 13 (equivalent to Example 11 of Patent Document 4), the temperature characteristic curve shifts to the low temperature side, the incremental permeability in the high temperature range is less than 2800, and an incremental permeability of more than 2800 cannot be obtained in the temperature range of -40 to 85°C.

[0100] <Case Equivalent to Patent Document 5: Comparative Example 14, Comparative Example 15>

[0101] As shown in Table 3 and Figure 7 As shown, it can be seen that in Comparative Example 14 (equivalent to Example 1 of Patent Document 5) and Comparative Example 15 (equivalent to Example 2 of Patent Document 5), the temperature characteristic curve is shifted to the high temperature side, the incremental permeability in the low temperature range is less than 2800, and the incremental permeability of 2800 or more cannot be obtained in the temperature range of -40 to 85°C. It can also be seen that the rate of change of the incremental permeability is large because Co is not added.

[0102] [Defective rate caused by abnormal grain growth]

[0103] Next, the defective rate caused by abnormal grain growth was investigated. For Inventive Examples 3, 11, 15, Comparative Examples 6, 8 and 13 to 18 shown in Table 4, ferrite pulverized powder was prepared in the same manner as described above, polyvinyl alcohol was added to the pulverized powder for granulation, a pressure of 118 MPa was applied, and a ring core was formed to form a molded body. After that, the molded body was placed in a sagger and loaded into a sintering furnace, and sintered at a maximum temperature of 1350°C to obtain a sintered body sample (core body) with an outer diameter of 6.0 mm × an inner diameter of 3.0 mm × a height of 4.0 mm. For the obtained sintered body sample, the initial magnetic permeability and incremental magnetic permeability were calculated using the above method. Furthermore, 100 sintered body samples were prepared, and the defective rate was calculated by visually inspecting the number of sintered body samples with abnormal grains of 0.5 mm or more on the surface of the sample. The results are shown in Table 4.

[0104] Here, Comparative Example 16 is set to have the same components as Example 7 of Patent Document 1, Comparative Example 17 is set to have the same components as Suitable Example 1 of Patent Document 2, and Comparative Example 18 is set to have the same components as Sample No. 1-5 (Invention Example) of Patent Document 3.

[0105] [Table 4]

[0106]

[0107] As shown in Table 4, in Inventive Examples 3, 11, and 15, the cores were made using ferrite powders having the conditions of the basic components and auxiliary components of the present invention, and an incremental magnetic permeability of 2800 or more was obtained in the temperature range of -40 to 85° C. It can be further seen that cores having abnormal grains were not produced, and the defect rate caused by abnormal grain growth was low.

[0108] As shown in Table 4, in Comparative Examples 6, 8, and 13 to 17, an incremental permeability of 2800 or more could not be obtained in the temperature range of -40 to 85°C, and the defective rate caused by abnormal grain growth was higher than that of the present invention. In addition, in Comparative Example 18, although an incremental permeability of 2800 or more could be obtained in the temperature range of -40 to 85°C, abnormal grain growth occurred, so there were defective cores, and the defective rate caused by abnormal grain growth was higher than that of the present invention.

[0109] [Process capability index Cpk]

[0110] Next, the process capability index Cpk of the present invention was investigated. In Invention Example 15 and Comparative Example 18, which have almost the same incremental permeability at -40°C, 100 sintered body samples (cores) were produced by the above method. The incremental permeability of each core was measured, and the standard deviation σ of the incremental permeability at -40°C, where the incremental permeability showed the lowest value, was found. Then, the lower limit specification of the incremental permeability at -40°C was set to 2700 (single-sided specification), and the process capability index Cpk taking into account the deviation was calculated according to the following formula (1). The results are shown in Table 5.

[0111] CpK = (average value - lower limit specification) / 3σ···(1)

[0112] [Table 5]

[0113]

[0114] As shown in Table 5, in Inventive Example 15 with a small content of Si or Ca, etc., Cpk is as high as 1.35, while in Comparative Example 18 with a large content of Ca, Cpk is as low as 0.82. From this result, it can be seen that Inventive Example 15 has a larger Cpk than Comparative Example 18, and has a margin relative to the lower limit of the specification of the incremental permeability. It can be seen that the incremental permeability defect rate of the present invention with a small content of Si or Ca, etc. is low compared to the conditions of the inventive example of Patent Document 3, and is therefore more preferred.

[0115] Industrial Applicability

[0116] According to the present invention, a MnZn ferrite suitable for electronic components such as pulse transformers can be obtained in a temperature range of -40 to 85°C, and the MnZn ferrite also exhibits a high incremental permeability when a DC magnetic field of 25 A / m is applied. This makes it possible to miniaturize the ferrite core and reduce the number of copper wire windings.

Claims

1. A MnZn ferrite, which is composed of a basic component, an auxiliary component and inevitable impurities, When the total amount of iron, zinc and manganese calculated as Fe2O3, ZnO and MnO is taken as 100 mol%, The basic ingredients are: Iron: 52.5-53.5 mol% calculated as Fe2O3; Zinc: 16.4 to 18.4 mol% calculated as ZnO; and Manganese: calculated as the balance in terms of MnO. Relative to the basic ingredients, the auxiliary ingredients are: Si: 30 to 100 mass ppm calculated as SiO2; Ca: 50 to 160 mass ppm calculated as CaO; Co: 1500 to 3500 mass ppm calculated as Co3O4; Nb: 100 to 600 mass ppm calculated as Nb2O5; and V: 100 to 600 mass ppm in terms of V2O5, The total content of the Nb and the V is 200 to 900 mass ppm in terms of Nb2O5 and V2O5.

2. The MnZn-based ferrite according to claim 1, wherein: The incremental magnetic permeability of the MnZn ferrite is above 2800 when a DC magnetic field of 25A / m is applied in a temperature range of -40 to 85°C. The temperature showing the maximum value of the incremental magnetic permeability is in the range of 10 to 50°C.

3. The MnZn-based ferrite according to claim 2, wherein: The incremental permeability of the MnZn ferrite is 3700 or more when a DC magnetic field of 25A / m is applied in a temperature range of 0 to 60°C. Furthermore, the MnZn-based ferrite has an incremental permeability of 4100 or more when a DC magnetic field of 25 A / m is applied in a temperature range of 23 to 40°C.

Citation Information

Patent Citations

  • Manganese-zinc ferrite

    JP2004319811A

  • MnCoZn FERRITE AND MAGNETIC CORE FOR TRANSFORMER

    JP2008143745A

  • Mn-Zn-BASED FERRITE AND MAGNETIC CORE FOR TRANSFORMER

    JP2013166663A

  • Ferrite composition, electronic component and power supply

    JP2022156991A